Proyecto de inversión para la elaboración y comercialización en la ciudad de Guayaquil de café hecho en base de habas. - Merchán Martínez, Grace (2010)
Nowadays the consumers worry more about their health, therefore, they look for healthful products and with nutritious contributions. With this project is desired to determine the economic feasibility to produce in Guayaquil cit,y a coffee made with beans one hundred percent natural. This product would be commercialized under the name of Nutricafé which will contain nutritious properties and will maintain the flavor of the traditional coffee; the consumers will be able to acquire it to a totally reasonable price in glass packages of 50 grams in the main supermarkets and local stores. By means of the realized studies, a potential market of 212,290 people was determined approximately, which represents to be very attractive for this industry. It is important to stress that in the local market there is any type of coffee done with beans, what means that there is not direct competition, only the locality of Zaruma some people prepare it for its own consumption, therefore they have not developed this idea far from it have started it up like an investment project.